Context-dependent modulation of spatial attention: prioritizing behaviourally relevant stimuli - Noah Britt; Jackie Chau; Hong-jin Sun (Cognitive Research)
Abstract Human attention can be guided by semantic information conveyed by individual objects in the environment. Over time, we learn to allocate attention resources towards stimuli that are behaviourally relevant to ongoing action, leading to attention capture by meaningful peripheral stimuli. A common example includes, while driving, stimuli that imply a possibly hazardous scenario (e.g. a pedestrian about to cross the road) warrant attentional prioritization to ensure safe proceedings. In the current study, we report a novel phenomenon in which the guidance of attention is dependent on the stimuli appearing in a behaviourally relevant context. Using a driving simulator, we simulated a real-world driving task representing an overlearned behaviour for licensed drivers. While driving, participants underwent a peripheral cue-target paradigm where a roadside pedestrian avatar (target) appeared following a cylinder cue. Results revealed that, during simulated driving conditions, participants (all with driver’s licenses) showed greater attentional facilitation when pedestrians were oriented towards the road compared to away. This orientation-specific selectivity was not seen if the 3-D context was removed (Experiment 1) or the same visual scene was presented, but participants’ viewpoints remained stationary (Experiment 2), or an inanimate object served as a target during simulated driving (Experiment 3). This context-specific attention modulation likely reflects drivers’ expertise in automatically attending to behaviourally relevant information in a context-dependent manner.